Eyewitness to jewish - Blech, Benjamin (John Wiley & Sons, 2004)
Featuring hundreds of excerpts from diaries, journals, letters, newspaper accounts, public testimony, official communications, and ancient documents such as the Torah, this unique chronicle provides memorable snapshots of daily life from biblical times to the modern day. These vivid and passionately written accounts, arranged in chronological order, transport you across space and time to witness crucial events from the birth of the Jewish people and the building and destruction of the two Temples to the Golden Age of Spain, the horrors of the Holocaust, the founding of the modern State of Israel, and important steps in the ongoing effort to achieve peace in the Middle East.